Mapuche Historiography: Colonized People Debating with Other Colonized People. Chile, 2006-2021; [Historiografía Mapuche: Colonizados Debatiendo Con Otros Colonizados. Chile, 2006-2021] - Canales-Tapia, P (Universidad Austral de Chile, 2025)
The history of the Mapuche people in Chile in recent decades has entered a new chapter: this time, from cities and universities, several generations of Mapuche thinkers and researchers have begun to write, debate, and participate in various forums regarding their own history and Chilean history, within frameworks theoretically marked by the weight of colonialism and decolonizing efforts in different spheres of this people’s actions. For this reason, we focus our attention on the last 15 years of production and discussion, largely due to the complexity of the temporal context studied and the Mapuche proposals that emerged during that period. Methodologically, this work is structured based on the historical method, the triangulation of sources, and documentary analysis, which reflects the emphases and rhythms of the debates in question. © 2025, Universidad Austral de Chile. All rights reserved.